Choosing Retrograde Intrarenal Surgery Versus Mini-Percutaneous Nephrolithotomy in Proximal Ureteric Stones - Shah, Rajiv; Adhikari, Deepak; Kandel, Tika Devi; Pandey, Sujan; Adhikari, Kapil (Journal of College of Medical Sciences-Nepal, 2024)
Background Proximal ureteric stone is one of the common presentations in renal stones disease. Safety, efficacy and stone free rate of retrograde intrarenal surgery and mini percutaneous nephrolithotomy are controversial. Thus, we aim to compare the efficacy, safety and stone free rates of two procedures. Methods This was a retrospective observational study including 60 cases divided into group A (Retrograde-intrarenal Surgery) and Group B (Mini-Percutaneous Surgery) between September 2022 to August 2023. Ethical approval was obtained from Institutional review Committee (Reference number: CMC-IRC/079/080-100). Convenience sampling was done. Results The mean age in group A was 43.83 ± 16.92 years and in group B was 46.33 ± 15.78 years with no significant p value (p = 0.112). Post operative haemoglobin changes in group A was 0.266 ± 0.279 gram% and in group B was 1.493 ±0.360 gram% with significant P value of 0.001. Similarly the duration of operation in Group A was 42.43± 13.783 minutes and in group B was 36.30 ± 7.173 minutes with significant P value 0.035. However the stone free rate was higher in group B than Group A without significant P value of 0.064. Both of the groups have minor post operative complication of fever and mild haeamaturia. Conclusions The stones clearance rate of mini percutaneous nephrolithotomy is better than retrograde intrarenal surgery and the safety of retrograde intrarenal surgery is higher than of mini percutaneous surgery.